2017
DOI: 10.1016/j.margeo.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation rhythms and hydrodynamics in two engineered environments in an open coast managed realignment site

Abstract: Managed Realignment (MR) schemes are considered by many coastal managers and engineers to be a preferable method of coastal flood defence and compensating for habitat loss, by creating new areas of intertidal saltmarsh and mudflat habitat. Monitoring of MR sites has tended to focus on short term ecological factors, resulting in a shortage of high frequency, high resolution long term measurements of the evolution of the sediment erosion, transportation, deposition and consolidation cycle (ETDC) in newly breache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…There has been a large amount of accretion in the vicinity of the creek networks forming at this site; Dale et al (2017) reported over 15 cm of accretion in the borrow pit adjacent to the area monitored here over a 1 year study period during the second year following site breaching. However, at Medmerry, creek formation was already occurring due to a difference in hydraulic head and sub-surface drainage, prior to the level of accretion reaching the critical 20-30 cm depth proposed, albeit site specifically, by Watts et al (2003).…”
Section: The Suitability Of Suas Technology For Measuring Embryonic Cmentioning
confidence: 73%
See 4 more Smart Citations
“…There has been a large amount of accretion in the vicinity of the creek networks forming at this site; Dale et al (2017) reported over 15 cm of accretion in the borrow pit adjacent to the area monitored here over a 1 year study period during the second year following site breaching. However, at Medmerry, creek formation was already occurring due to a difference in hydraulic head and sub-surface drainage, prior to the level of accretion reaching the critical 20-30 cm depth proposed, albeit site specifically, by Watts et al (2003).…”
Section: The Suitability Of Suas Technology For Measuring Embryonic Cmentioning
confidence: 73%
“…This site was selected as it allowed for analysis of creek development in a rapidly evolving nearbreach environment. Tidal data, reported by Dale et al (2017), indicated that the bank would typically be inundated for 2.5 h by approximately 0.70 m (spring tides) and 0.30 m (neap tides) of water per tidal cycle (Fig. 2).…”
Section: Study Sitementioning
confidence: 91%
See 3 more Smart Citations